Analysis of the Internal Control System in an Effort to Prevent Fraud in Trade Goods Inventory at Minimarket Omi Kawan Hinca Bandar Island - Siti Nur Adillah; Wahyu Syarvina; Hotbin Hasugian (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The internal control system at Minimarket Omi Kawan Hinca Bandar Pulau is implemented to determine whether the management system has been implemented properly or not and to avoid fraud in the inventory of goods. The internal control system carried out at Minimarket Omi Kawan Hinca Bandar Pulau in terms of separation of duties and authority is still not running optimally with evidence of multiple positions. It is feared that there will be abuse of position authority which results in fraud. The internal control system is expected to prevent fraud that will occur. What this research aims to achieve is to analyze the effectiveness of the implementation of the internal control system as an effort to control or even prevent fraud. The qualitative method was applied in this study using data collection techniques carried out through observation and interviews. The results of this study are that the internal control system over merchandise inventory at Minimarket Omi Kawan Hinca Bandar Pulau has been implemented according to the components of internal control over inventory, but it is still not implemented optimally and internal control over inventory may be quite good but not effective in preventing fraud in inventory management.